P057 INFLIXIMAB TREATMENT INTENIFICATION BASED ON ENDOSCOPIC ACTIVITY CONTRIBUTES TO CLINICAL RESPONSE IN PATIENTS WITH CROHN'S DISEASE. (7th February 2019) - Tanaka, Akihito; Kanmura, Shuji; Komaki, Yuga; Sasaki, Fumisato; Nasu, Yuichiro; Sameshima, Yohichi; Nakamura, Yuichi; Tokushige, Koichi; Ohi, Hidehisa; Sameshima, Yukinori; Ido, Akio
Abstract: Background and aim: Infliximab (IFX) treatment intensification, consisting of dose escalation or interval shortening, is effective for restoring clinical response in patients with Crohn's disease (CD). However, clinical data on the timing of IFX treatment intensification are sparse. We aimed to evaluate the timing of IFX treatment intensification for clinical response in patients with CD. Methods: A retrospective multicenter cohort study was conducted. It included 243 patients with CD, of whom 154 were on IFX maintenance therapy between February 2002 and July 2018. Eighty-five patients became clinically unresponsive during IFX maintenance therapy, and 51 patients received a double dose of IFX (10 mg/kg) or the next infusion after a shorter interval. Other patients were switched to a different therapeutic regimen. Treatment intensification due to aggravation of "clinical symptoms" were defined as CS group, whereas intensification due to "endoscopic imaging" findings was defined as EI group. The persistence rate and the corticosteroid-free remission rate were analyzed 6 months after treatment was changed. Results: The 51 patients who received treatment intensification included 32 men and 19 women with a median age of 42 years (range, 15–78 years), of whom 72.5% were clinically responsive for 6 months. Twenty-eight patients (78%) underwent dose escalation. Eight patients (22%) underwent interval shortening. There were no significant differences in short-term effects between the dose escalation and interval shortening groups (p=1.000). The 15 patients in the EI group had a significantly higher rate of clinical response (93.3%) than the 36 patients in the CS group (63.9%) (p=0.041) Conclusion: In a retrospective multicenter study, IFX treatment intensification based on endoscopic imaging was more effective for improving CD activity than treatment intensification based on symptoms alone in patients with active CD.